Islam and tourism: cultural diversity management - Hassan, Sayed Hassan Eslam (“KROK” University, 2021)
At the present stage, international tourism is one of the promising areas, in particular the economic activity of many countries. It is known that the tourism business accounts for 7% of global exports of goods and services, second only to revenues from exports of oil, petroleum products and automotive.